Cader Phenomena as a Determining Group for the Success of Sustainable Development in Rural Areas - Moh. Dulkiah (UIN Sunan Gunung Djati, 2023)
This research examines how the cadre phenomenon as a group determines the success of a sustainable development program in rural areas. This research uses a qualitative approach with descriptive methods. Research data collection was carried out through observation and in-depth interviews with development cadres, government apparatus, community leaders, youth leaders, religious leaders, and the community in the 3 (three) research villages, namely Cidenok Village, Sumberjaya Village, and Garawangi Village, which all three are part of Sumberjaya District, Majalengka Regency, West Java Indonesia. This study found that cadres are one of the determining groups for the success of sustainable development programs in rural areas. The participation of cadres is seen not only in aspects of the government but also in community activities. Cadres who have fast, active, and good adaptation and apply core values can be trusted by the community in disseminating development information and inviting active participation. The success of sustainable development goals (SDGs) in rural areas requires the role of stakeholders both horizontally and vertically between the community and the government. This study concludes that the involvement of cadre groups has a significant role in the successful implementation of the sustainable development program in rural areas.